Warfarin or dabigatran for treatment of atrial fibrillation. (19th June 2014) - Poller, L.; Jespersen, J.; Ibrahim, S.; the European Action on Anticoagulation (EAA)
Summary Background New antithrombotic drugs for prevention and treatment of thromboembolic disorders in AF that are less demanding on local staff and facilities than warfarin should be welcomed if proved successful. Objectives The comparative value and possible dangers of substituting the new drug dabigatran as a replacement remain to be established. Its safety and effectiveness must be reviewed and assessed by further study. Methods Clinical results of the European Action on Anticoagulation (EAA) computer‐assisted dosage study and the Randomized Evaluation of Long‐Term Anticoagulation Therapy (RE‐LY) trial have been compared. Results Clinical events were lower in patients on warfarin in the EAA study compared to patients on both warfarin and dabigatran in the RE‐LY study. Conclusion Evaluations should recognize optimum requirements for safe and effective administration of both types of drug. In the warfarin arm improvements in effectiveness and safety recently introduced (i.e. the PT/INR line and variance growth analysis) should be included as they have been shown to be successful in improved prediction of bleeding and further thromboembolism. The incidence of bleeding with dabigatran, for which there is no antidote, will require evaluation.